A facile preparation of sulfur doped nickel–iron nanostructures with improved HER and supercapacitor performance. (8th February 2022) - Choi, Jonghyun; Nkhama, Alfred; Kumar, Anuj; Mishra, Sanjay R.; Perez, Felio; Gupta, Ram K.
Abstract: Since the use of diverse synthesis approaches can induce the variation in the density of active sites, which impacts electrocatalytic performance, the strategy utilized to fabricate the electrode materials for energy devices is just as important as the materials themselves. Herein, porous NiFe-oxide nanoflowers (NiFe-NFs) and macroparticles (NiFe-MPs) and corresponding S-doped NiFe-oxide nanoflowers (NiFeS-NFs) and macroparticles (NiFeS-MPs) were fabricated using facile co-precipitation and hydrothermal-sulfurization strategies, respectively. The prepared NiFe-NFs, NiFeS-NFs, NiFe-MPs, and NiFeS-MPs materials were investigated for their electrocatalytic HER in 1 M KOH electrolyte. The results indicated that NiFe-NFs displayed an overpotential of 177 mV @ 10 mA/cm 2 for HER, whereas the NiFe-MPs, having similar composition, exhibited a high HER overpotential of 187 mV @ 10 mA/cm 2 . The enhanced HER catalytic performance of NiFe-NFs was attributed to the extensive exposure of active sites at the edges and vertices of nanocubes in the NFs-architecture. Moreover, after sulfurization, NiFeS-NFs and NiFeS-MPs demonstrated a considerable enhancement in their HER activity (54 mV and 152 mV @ 10 mA/cm 2, respectively) as compared to un-sulfurized materials, which can be attributed to the enhanced conductivity of materials after S-doping, as supported by theoretical studies. Further, the capacitance experiments showed a significant increment in specific capacitances of NFs and MPs after sulfurization, from 69 to 604 F/g and from 185 to 514 F/g, respectively. This work shows that morphological and compositional changes in metal oxide-based materials may considerably enhance their catalytic activity and capacitance. Graphical abstract: Image 1 Highlights: A facile strategy is developed to prepare bimetal oxides/sulfer doped bimetal oxides. Prepared S-doped/undoped NiFe-oxides possessed nanoflowers/macroparticles morphologies. Prepared NiFeS-oxide with nanoflowers morphology showed excellent OER and HER. Prepared nanoflowers type NiFeS-oxide exhibited remarkable charge storage capacilty.